The moderating role of socioeconomic status on the relationship between teacher social support and sense of belonging to school. (17th September 2022) - Bakchich, Julien; Carré, Arnaud; Claes, Nele; Smeding, Annique
Abstract: Background: Teacher social support (TSS) has been identified as one of the most important factors of success and well‐being for students. Yet, there is a gap in the literature regarding the impact of students' socioeconomic status (SES) on their perceptions of TSS, and whether SES may impact the strength of the relationship between teacher social support and students' sense of belonging to school (SBS). Aims: In this preregistered study, we aimed at filling this gap by testing the moderating role of SES on the TSS‐SBS link, along with the direct associations between these variables. Sample: We used data from the French sample of the Programme for International Student Assessment 2018 (PISA; N = 6308). Methods: TSS was primarily assessed as a latent construct based on three indicators provided by PISA: teacher support, teacher emotional support and teacher feedback. Regarding SES, we primarily focused on family wealth possessions and parents' highest level of education. Results: Using structural equation modelling, findings confirmed that the TSS‐SBS link was stronger for high‐SES than low‐SES students. We also found a negative association between teacher support and SES. Importantly, preregistered additional analyses highlight that findings depend on the SES and TSS indicators considered. Conclusions: Findings support the importance of SES effect on students' perceptions of their interactions with teachers and the extent to which they perceive they belong to the school. The implications and limitations of this research are discussed.